부인암 환자의 하지 림프부종 예방과 관리를 위한 간호실무 프로토콜 개발 - 이현정(Lee, Hyunjung); 전나미(Chun, Nami); 노기옥(Noh, Gieok); 송현주(Song, Hyunju); 김주현(Kim, Juhyun); 하수미(Ha, Sumi) (Asian oncology nursing, 2018)
Purpose: This study aimed to develop and evaluate the lower extremity lymphedema nursing practice protocol for patients following gynecologic cancer treatment. Methods: Thirteen web-sites were searched for eligible clinical practice guidelines (CPGs) and eleven databases were searched to identify evidence to develop a lower extremity lymphedema nursing practice protocol for patients following gynecologic cancer treatment. Results: Based on the inclusion and exclusion criteria, eight CPGs and ninety-six studies, two guidelines and eight studies were identified as evidence. The protocol development group consisted of ten experts who have at least five years’ experience in the related area. A lower extremity lymphedema nursing practice protocol for patients following gynecologic cancer treatment was developed including forty-three recommendations in five domains. Significant differences were found in nurses’ pre and post knowledge and confidence on lower extremity lymphedema prevention and management. Conclusion: Nurses and other professionals could utilize this evidence based lower extremity lymphedema nursing practice protocol and apply it to patients undergoing gynecologic cancer treatment. KCI Citation Count: 0